A new approach of assessing patient safety aspects in routine practice using the example of "doctors handwritten prescriptions". Issue 7 (7th January 2019) - Sendlhofer, Gerald; Pregartner, Gudrun; Gombotz, Veronika; Leitgeb, Karina; Tiefenbacher, Peter; Jantscher, Lydia; Richter, Christian; Hoffmann, Magdalena; Kamolz, Lars P.; Brunner, Gernot
Abstract: Aims and objectives: To test the method of self‐ and external assessment as a feedback system to decrease illegibility and incorrectness of handwritten prescriptions and to reduce additional workload for nursing staff. Background: Illegibility and incorrectness of handwritten prescriptions occur very often and are the most crucial factors affecting patient safety. Design: Self‐ versus external assessment using a 15 items checklist. Methods: Nurses randomly selected five fever charts of their wards. Each fever chart was self‐ as well as externally assessed. Nurses and doctors took part in the self‐assessment, and the external assessment was performed by external experts. According to a monitor suspension system, assessment results were considered "green, " "yellow" or "red." After the first assessment and issuing feedback of the results "red" scored wards by the external assessment, additional trainings were performed. Thereafter, a second assessment was performed to rate eligibility and completeness of prescriptions. The research and reporting methodology followedsquire 2.0. Results: In total, 580 fever charts were self‐ as well as externally assessed (290 in each of the two assessment periods). Out of the 58 participating wards, 31 were surgical and 27 were non‐surgical wards. Averaging over all checklist items, surgical and non‐surgical wards improved only slightly over time. Linear regression models for ward means showed that there were significant improvements over time for non‐surgical wards. Conclusions: This method directly involves those who commit errors and stimulate learning from errors. The approach of self‐ and external assessment was a useful instrument to detect inadequate prescriptions and to monitor improvements. Relevance to clinical practice: Significant improvements were achieved regarding correctness and legibility of handwritten prescription and helped to decrease additional workload for nursing staff and thereby enhanced patient safety.